2013
DOI: 10.1037/a0030771
|View full text |Cite
|
Sign up to set email alerts
|

Examining a model of life satisfaction among unemployed adults.

Abstract: The present study examined a model of life satisfaction among a diverse sample of 184 adults who had been unemployed for an average of 10.60 months. Using the Lent (2004) model of life satisfaction as a framework, a model was tested with 5 hypothesized predictor variables: optimism, job search self-efficacy, job search support, job search behaviors, and work volition. After adding a path in the model from optimism to work volition, the hypothesized model was found to be a good fit for the data and a better fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 73 publications
7
66
0
2
Order By: Relevance
“…Specifically, one previously published study used a subset of this data-set to examine predictors of life satisfaction among unemployed adults, assessing the roles of work volition, job search self-efficacy, job search behaviors, optimism, and job search support (Duffy, Bott, Allan, & Torrey, 2013). In the current study, we do not analyze any of the same variables, have completely different research questions, and only analyze the data of involuntarily unemployed participants, whereas the published study examined all unemployed participants.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, one previously published study used a subset of this data-set to examine predictors of life satisfaction among unemployed adults, assessing the roles of work volition, job search self-efficacy, job search behaviors, optimism, and job search support (Duffy, Bott, Allan, & Torrey, 2013). In the current study, we do not analyze any of the same variables, have completely different research questions, and only analyze the data of involuntarily unemployed participants, whereas the published study examined all unemployed participants.…”
Section: Methodsmentioning
confidence: 99%
“…This research has shown that work volition may have a direct relation to the job satisfaction of employed workers (Duffy et al 2013c) and the life satisfaction of unemployed workers (Duffy et al 2013b). The research has also identified some interesting moderator effects of volition.…”
Section: Well-being: Positive Adaptation To School and Work Settingsmentioning
confidence: 95%
“…The research has also identified some interesting moderator effects of volition. Duffy et al (2013b) found that perceived organizational support was more strongly related to job satisfaction among those with lower versus higher volition. Dik & Hansen (2011) also demonstrated that a volition-like variable (perceived control over the work environment) moderated the relationship between P-E congruence and job satisfaction.…”
Section: Well-being: Positive Adaptation To School and Work Settingsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Lent, Brown, and Hackett's (1994) Social Cognitive Career Theory has been the focus of over 200 studies in less than two decades, including those done by the authors themselves. Some researchers are branching out to new populations, such as unemployed adults (Duffy, Bott, Allan, & Torrey, 2013), cancer survivors (Nicholas, 2013), children (Cipriano, Skowron, & Gatzke-Kopp, 2011), and to new settings such as schools (Baskin et al, 2010). Others have investigated within group differences for African Americans (Byars-Winston, 2006) Latinos (Galván, Buki, & Garcés, 2009), Asian Americans (Wang & Kim, 2010), American Indians (Thompson, Johnson-Jennings, & Nitzarim, 2013), low SES high school students (Kenny, Walsh-Blair, Blustein, Bempechat, & Seltzer, 2010) and sexual minorities (Szymanski & Ikizler, 2013).…”
mentioning
confidence: 97%